(untitled) (Hoboken, N.J, 2007)
This is the most authoritative archive of Barry Boehm's contributions to software engineering. Featuring 42 reprinted articles, along with an introduction and chapter summaries to provide context, it serves as a "how-to" reference manual for software engineering best practices. It provides convenient access to Boehm's landmark work on product development and management processes. The book concludes with an insightful look to the future by Dr. Boehm
Keywords: Software engineering,Computer programming,Computer software,Kỹ nghệ máy tính; Management,Development